Alexandre’s Education: Wit and War Alexandre de paris' Roman d'alexandre (c. 1180) - Pérez-Simon, Maud (Troianalexandrina, 2011)
Abstract The historical Alexander the Great is celebrated for his campaigns of conquest in the East. Educated by Aristotle, and raised to be king by his father, he proved himself able to understand and rule the world he discovered. During the Middle Ages, Alexandre de Paris wrote a novelized account of Alexander the Great's life. An underlying narrative thread in this version highlights Aristotle's teachings —both through the expected medieval curriculum and through empirical instruction— on how to battle and rule by wit as much as by brute force. In episode after episode, Alexander the Great learns to master his emotions, language and knowledge in order to develop a strategy of power/force based on intelligence and subtlety, especially as related to speech. His use of wit and of double-meaning in speech to govern became legendary. This article discusses the fundamental importance of education in making the Alexander saga an effective political example and counter example, a true Mirror for Princes, for rulers during the Middle Ages.